2006
DOI: 10.2754/avb200675020175
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Blood Serum Concentrations of Immunoglobulin IgG, IgA and IgM Isotypes in Suckling Foal

Abstract: Postnatal changes in concentrations of immunoglobulin IgG, IgM and IgA isotypes from birth until the age of five months were monitored by the ELISA method. The experiment was performed in a group of 52 thoroughbred foals and their mothers. Among the investigated animals, failure of colostral immunity transfer was recorded in only four foals (7.7 percent). The concentrations of immunoglobulin IgG and IgA isotypes primarily decreased during the first weeks of life and then gradually increased until the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
4
5
0
2
Order By: Relevance
“…In agreement with the current study, onset of IgA synthesis in foals has been reported to occur at approximately 1-2 months of age [18]. Mean periparturient mare serum IgA concentrations were comparable with values reported in a small group of Thorougbred mares [11] and another of mixed-breed horses [16] but lower than a study of 27 mixed-breed adults [14]. In contrast, colostrum and milk concentrations of IgA were found to be lower than those described in previous studies [11,16].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the current study, onset of IgA synthesis in foals has been reported to occur at approximately 1-2 months of age [18]. Mean periparturient mare serum IgA concentrations were comparable with values reported in a small group of Thorougbred mares [11] and another of mixed-breed horses [16] but lower than a study of 27 mixed-breed adults [14]. In contrast, colostrum and milk concentrations of IgA were found to be lower than those described in previous studies [11,16].…”
Section: Discussionsupporting
confidence: 92%
“…The concentrations of IgA measured in Australian Thoroughbreds are comparable to those found in in a study of 52 European Thoroughbred foals . The rapid reduction of IgA concentration in the foal serum from 12 h to 19 days after parturition is likely due to gut closure and utilisation of passively transferred IgA and is consistent with the response observed for IgG .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Most studies are focused predominantly on IgG instead of total Ig because of their concentration in serum; this is due to the function of IgG, most of which is absorbed and protect the newborn foal from systemic infections (Sedlinská et al, 2006). These results may be explained by major ontogenetic impacts on the quality of mammary gland secretions (Chavatte-Palmer et al, 2002), which was also observed in our experiment.…”
Section: Discussionsupporting
confidence: 60%
“…Foals, calves and piglets are born without placental transfer of Ig from the mother to the fetus and are agammaglobulinaemic at birth. They are therefore solely dependent on intestinal uptake of Ig from colostrum for passive immunization (Curadi et al., 2001; Sangild, 2003; Sedlinská et al., 2006). Likewise, placental transfer of fat‐soluble vitamins, such as vitamin E, is limited (Lauridsen and Jensen, 2007).…”
Section: Introductionmentioning
confidence: 99%